The Anti-Restrictions Movement and the Populist Counterpublics in Denmark - García Agustín, Óscar; Nissen, Anita (PARTECIPAZIONE E CONFLITTO, 2023)
Despite less restrictive governmental Covid-19 measures than in other European countries, Denmark also witnessed the rise of mobilisations against vaccine measures and corona-related restrictions. While most protests did not assemble many participants, nor garnered much media attention, the anti-restrictions scene consists of a vast and diverse array of activists and organisations united in the call for less governmental intervention in the freedoms of the citizens, as also witnessed elsewhere across the globe. We conceptualise the anti-restrictions groups as ’populist counterpublics’, since the counterdiscourses emerging from the Covid-19 measures deepen the antagonist divide between the ordinary people and the elites. We focus on three of the most prominent groups: Men in Black (MIB), the Freedom Movement’s Joint Council (FBF), and Earth Freedom Knowledge 21 (JFK21). By analysing arenas and frames, we show how the Danish anti-restrictions movement uses the diagnostic frames of totalitarian government and global complot to blame the Danish government and international elites, and the prognostic frames of power and rights to the people and individual freedom as solutions to the articulated problems. Although these groups employed similar frames and enemy constructions, they failed in promoting internal alliances and in shaping a new and accepted idea of who makes up ’the people’, leading to a limited level of public support for their cause.